2012
DOI: 10.1186/1746-1596-7-57
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathologic association of c-MET overexpression in Iranian gastric carcinomas; an immunohistochemical study of tissue microarrays

Abstract: Backgroundc-MET is an oncogene protein that plays important role in gastric carcinogenesis and has been introduced as a prognostic marker and potential therapeutic target. The aim of this study was to evaluate the frequency of c-MET overexpression and its relationship with clinicopathological variables in gastric cancer of Iranian population using tissue microarray.MethodsIn a cross sectional study, representative paraffin blocks of 130 patients with gastric carcinoma treated by curative gastrectomy during a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
(71 reference statements)
2
24
0
Order By: Relevance
“…The immunohistochemical staining of the GFAB and NFP antigen was performed on sections prepared from formalin-fixed paraffin-embedded tissues (FFPE) as described previously (Madjd et al, 2011;Sotoudeh et al, 2012;Gheytanchi et al, 2014;Keymoosi et al, 2014). Polyclonal rabit anti-human glial fibrillary acidic protein (GFAP) (Code No.Z0334, Dako, Denmark); and monoclonal mouse anti-human neurofilament NE14 (anti-NF, clone NE14, BioGenex, The Netherlands), which reacts with the 200-kilodalton component of this protein (NFP), was used as a primary antibodies.…”
Section: Immunohistochemistery Analysismentioning
confidence: 99%
“…The immunohistochemical staining of the GFAB and NFP antigen was performed on sections prepared from formalin-fixed paraffin-embedded tissues (FFPE) as described previously (Madjd et al, 2011;Sotoudeh et al, 2012;Gheytanchi et al, 2014;Keymoosi et al, 2014). Polyclonal rabit anti-human glial fibrillary acidic protein (GFAP) (Code No.Z0334, Dako, Denmark); and monoclonal mouse anti-human neurofilament NE14 (anti-NF, clone NE14, BioGenex, The Netherlands), which reacts with the 200-kilodalton component of this protein (NFP), was used as a primary antibodies.…”
Section: Immunohistochemistery Analysismentioning
confidence: 99%
“…Moreover, MET overexpression was more frequently detected in dysplasia and precancerous gastric lesions than in intestinal metaplasia [21] . MET overexpression has frequently been found in intestinal type or differentiated type cancers [12,14,22,23] , although one study reported a correlation with diffuse type [13] . Retterspitz reported that MET was overexpressed in 51% (45 of 88) of diffuse type tumors [24] .…”
Section: Protein Expression On Immunohistochemistrymentioning
confidence: 99%
“…Retterspitz reported that MET was overexpressed in 51% (45 of 88) of diffuse type tumors [24] . MET overexpression has been significantly associated with tumor invasion depth [12,13,23] , lymph-node metastasis [12,13,19,20,25,26] , distant metastasis [12,13,25] , tumor stage [12,20,23,26] , and recurrence [14] , although several studies found no relation to any clinicopathological factors [24,27,28] . MET overexpression correlated with liver metastasis only in stage Ⅳ disease [29] .…”
Section: Protein Expression On Immunohistochemistrymentioning
confidence: 99%
“…Breast cancer tissue microarrays were prepared as described previously (Kononen et al, 1998;Mehrazma et al, 2012;Sotoudeh et al, 2012;Mohsenzadegan et al, 2013). All cases were reviewed and the tumor area was marked on their H&E stained slides.…”
Section: Tissue Microarray (Tma) Preparationmentioning
confidence: 99%